Origin and Prediction of Highly Specific Bond Cleavage Sites in the Thermal Activation of Intact Protein Ions. Issue 3 (11th December 2018) - Wang, Huixin; Leeming, Michael G.; Ho, Junming; Donald, William A.
Abstract: Predicting the fragmentation patterns of proteins would be beneficial for the reliable identification of intact proteins by mass spectrometry. However, the ability to accurately make such predictions remains elusive. An approach to predict the specific cleavage sites in whole proteins resulting from collision‐induced dissociation by use of an improved electrostatic model for calculating the proton configurations of highly‐charged protein ions is reported. Using ubiquitin, cytochrome c, lysozyme and β‐lactoglobulin as prototypical proteins, this approach can be used to predict the fragmentation patterns of intact proteins. For sufficiently highly charged proteins, specific cleavages occur near the first low‐basicity amino acid residues that are protonated with increasing charge state. Hybrid QM/QM′ (QM=quantum mechanics) and molecular dynamics (MD) simulations and energy‐resolved collision‐induced dissociation measurements indicated that the barrier to the specific dissociation of the protonated amide backbone bond is significantly lower than competitive charge remote fragmentation. Unlike highly charged peptides, the protons at low‐basicity sites in highly charged protein ions can be confined to a limited sequence of low‐basicity amino acid residues by electrostatic repulsion, which results in highly specific fragmentation near the site of protonation. This research suggests that the optimal charge states to form specific sequence ions of intact proteins in higher abundances than the use of less specific ion dissociation methods can be predicted a priori. Abstract : Specific bond cleavage of highly charged protein ions can result from the protonation of low‐basicity amino acid residues. An approach to predict the specific cleavage sites in whole proteins was developed, using ubiquitin, cytochrome c, lysozyme, and β‐lactoglobulin as prototypical proteins.